Acceptability of a digital patient notification and linkage-to-care tool for French PrEPers (WeFLASH©): Key stakeholders' perspectives. (December 2019) - Lessard, David; Aslan, Alexandre; Zeggagh, Jérémy; Morel, Stéphane; Michels, David; Lebouché, Bertrand
The objective of this study was to describe stakeholders' perspectives on the acceptability of WeFLASH © (AADISS, Paris, France), a digital smartphone sexually transmitted infection (STI) patient notification (PN) tool to be launched among French HIV pre-exposure prophylaxis users (PrEPers). In Paris, Lyon, and Nice, we conducted 2-hour focus group discussions with PrEPers (n = 21) and community mediators (n = 10), and one-on-one interviews with PrEP-prescribing physicians (n = 5) and HIV/STI management decision-makers (n = 4). Recordings were transcribed. The analysis focused on perceived benefits and risks. Concerning benefits, participants mentioned that WeFLASH © could provide: improved PN and STI screening, by refining the notification of anonymous partners; customized linkage-to-care, by providing users with tailored information on care; and transferable epidemiological data, by filling a need for real-time data. Participants anticipated risks for: privacy and confidentiality and suggested specific security settings to protect users' identity; sexual behavior and suggested game-like functions to improve the integration of the tool in sexual contexts; and fairness and emphasized the importance of making WeFLASH © accessible to all men who have sex with men. WeFLASH © could facilitate PN for an increasing proportion of anonymous partners met online, and empower users, including notified partners, on questions of confidentiality and consent, access to STI prevention and screening services, and access to data.